2012
DOI: 10.1104/pp.112.206656
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in a Very-Long-Chain Fatty Acid β-Ketoacyl-Coenzyme A Synthase of Tomato Impairs Microgametogenesis and Causes Floral Organ Fusion  

Abstract: Previously, it was shown that β-ketoacyl-coenzyme A synthase ECERIFERUM6 (CER6) is necessary for the biosynthesis of very-long-chain fatty acids with chain lengths beyond C₂₈ in tomato (Solanum lycopersicum) fruits and C₂₆ in Arabidopsis (Arabidopsis thaliana) leaves and the pollen coat. CER6 loss of function in Arabidopsis resulted in conditional male sterility, since pollen coat lipids are responsible for contact-mediated pollen hydration. In tomato, on the contrary, pollen hydration does not rely on pollen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 56 publications
2
48
0
1
Order By: Relevance
“…Similar observations have been made in maize (Zea mays) and in rice (Oryza sativa) (Jenks et al, 2002;Islam et al, 2009). In addition, no organ fusion was observed among all the glossy/dull fruit mutants studied, in contrast with the glossy mutants described in Arabidopsis or the SlCER6 loss-offunction wax tomato mutant (Smirnova et al, 2013). Although the participation of wax in the glossy aspect of the fruit cannot be excluded (several glossy mutants display significant increases in wax load), our results strengthen the conclusion that the glossy/dull fruit appearance in our tomato mutants is not due to wax deficiency.…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propsupporting
confidence: 69%
“…Similar observations have been made in maize (Zea mays) and in rice (Oryza sativa) (Jenks et al, 2002;Islam et al, 2009). In addition, no organ fusion was observed among all the glossy/dull fruit mutants studied, in contrast with the glossy mutants described in Arabidopsis or the SlCER6 loss-offunction wax tomato mutant (Smirnova et al, 2013). Although the participation of wax in the glossy aspect of the fruit cannot be excluded (several glossy mutants display significant increases in wax load), our results strengthen the conclusion that the glossy/dull fruit appearance in our tomato mutants is not due to wax deficiency.…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propsupporting
confidence: 69%
“…Previous studies have shown that a defective cuticle often causes postgenital fusion (Kurdyukov et al, ; Shi et al, ; Smirnova et al, ). To test whether loss of function of HSP70‐16 changes cuticle properties and chemical profiles in floral organs, we performed floral organ surface characterization using SEM and TEM and sepal wax and cutin composition assays using GC‐MS and GC‐FID.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been observed in a wax-deficient tomato mutant (Smirnova et al, 2013), a range of Arabidopsis mutants with abnormal cuticles (Yephremov et al, 1999;Wellesen et al, 2001;Kurdyukov et al, 2006a;Bird et al, 2007), and transgenic Arabidopsis plants overexpressing a secreted fungal cutinase (Sieber et al, 2000). The fusion zones are often marked by two adjacent polysaccharide cell walls with no visible cuticle separating the two organs, although the fused epidermal layers maintain their identity, as indicated by the differentiation of internal nonfunctional stomata within fusion zones (Sieber et al, 2000).…”
Section: The Cuticle and Developmentmentioning
confidence: 99%